Are employability skills learned in US youth education and training programs? - Robert I. Lerman (IZA Journal of Labor Policy, 2013)
Skills are a central source of high productivity and economic well-being. But what do we mean by productive skills? Both with regard to measurement and policy, the primary focus in the U.S. has been on academic skills, as measured by tests of reading, writing and math abilities and by educational attainment, including degrees completed. However, a new consensus is emerging that an array of non-academic skills and occupational skills may be at least as important for labor market success. After reviewing the evidence on respective roles of various types of skills required by employers, this paper examines the skill-enhancing effects of several youth programs and demonstrations, with an emphasis on how well these efforts raise non-academic skills directly through purposeful activities or indirectly as a result of other employment-enhancing services.
Keywords: I28; J08; J24; 330; skills; youth; training